IMPROVING STUDENTS' SCIENTIFIC ARGUMENTATION SKILLS THROUGH PROBLEM-BASED LEARNING: PENINGKATAN KETERAMPILAN ARGUMENTASI ILMIAH MAHASISWA MELALUI PEMBELAJARAN BERBASIS MASALAH - Yunus, Muh. Rizal Kurniawan (Jurnal Biogenerasi, 2024)
The inability of students to construct coherent arguments supported by scientific evidence in the discussion process shows that students' scientific argumentation skills are low in the Introduction to Education course. This problem demands improvements in the implementation of the learning process by implementing learning models that can train and develop students' scientific argumentation skills. The application of the Problem Based Learning model is a collaborative learning model which in theory can help students improve their argumentation skills. In this research, we will examine improving students' scientific argumentation skills through the Problem Based Learning learning model. This research is classroom action research (PTK) which was carried out in the odd semester of the 2023/2024 academic year with 22 research subjects. The research was carried out in two cycles, where each cycle consisted of planning stages, action implementation, observation and reflection. The results of the research showed that in cycle I there was an increase with an N-gain value of 0.05, which showed that the increase was still within the low criteria, so it was continued in cycle II which showed an increase with an N-gain value of 0.8, which means there had been an increase in the high category. So it is concluded that there is an increase in students' scientific argumentation skills who are taught using the Problem Based Learning learning model.